Uso da fibrina rica em plaquetas e leucócitos (l-prf) em modelo in vivo de osteonecrose dos maxilares associada ao uso de bisfosfonatos (onmab):estudo de boca dividida - Perussolo, José Maurício (2021)
The aim of this study was to evaluate the use of platelet and leukocyte-rich fibrin membranes (L-PRF) in alveolar repair in the presence of osteonecrosis. In this work, twelve Wistar rats (six males and six females), approximately twelve months old and 500 g in weight were used. A split-mouth study was performed, the right side was used as treatment, with insertion of platelet and leukocyte-rich fibrin membranes, L-PRF (GLPRF group), and the left side received no intervention for control (control group, CG ). The application of zolendronate (via caudal) took nine weeks. The surgery was divided into two stages: 1) in the eighth week of zolendronate application, extraction of the lower first molars on both sides was performed, associated with bone decorticalization. In the ninth week of zolendronate application, extractions of the lower second molars were performed on both sides, followed by bone decorticalization. To make the L-PRF membranes, 1 ml of blood was removed through cardiac puncture. Two animals did not resist cardiac puncture and the collection of blood from one of the animals was not enough to form the membrane, so they were excluded from the study, leaving 9 individuals. The following clinical variables were observed: presence of bone exposure, presence of inflammation (edema, erythema), suppuration, bone sequestration and alveolar epithelialization. In addition, the measurement of the size of the mesiodistal (M-D) and buccolingual (V-L) bone exposure was measured with the aid of a millimeter probe. Statistical analysis was performed using the Statistical Package for Social Science program (SPSS, version 27.0; SPSS) using Fisher's exact test, with a significance level of 0.05. There were no significant differences between sides regarding the presence of bone exposure, presence of inflammation, suppuration, bone sequestration and alveolar epithelialization (p > 0.05). Lower bone exposure was observed in the M-D (p = 0.002) and V-L (p = 0.03) directions. It can be concluded that the use of PRF reduces the repair time of alveoli in necrosis, further studies with a larger sample of animals may be necessary.